Evaluation of High-Temperature Heat Pumps’ Potential to Replace Gas Boilers in Industrial Buildings - Talaba Ovidiu; Serban Alexandru; Hiris Paul Daniel; Balan Mugur Ciprian (E3S Web of Conferences, 2025)
The study proves that high-temperature heat pumps with CO2 of air to water type, in monobloc construction, can replace the gas boilers for heating and DHW, in an industrial building. The most efficient configuration is proposed with 3 heat pumps of 250 kW nominal thermal power is capable to provide 81 % of the annual thermal energy and 3 electric boilers of 720 kW total thermal power to produce the remaining 19 % of the annual thermal energy. The COP of the heat pumps decreases if the number of heat pumps increases. A single heat pump will achieve an annual COP of 2.66 without the PV system while in the proposed configuration with 3 heat pumps, the annual COP will be 2.37 without the PV system. The payback period for the configuration with 3 heat pumps is 3.10 years without the PV system and 3.26 years with the PV system.